Workforce Transformation in Industry 4.0: Bridging Skills Gaps and Enhancing Collaboration in Vietnam - Sharma, Richa; Vaka, Dilip Kumar; Azmeera, Rajesh (Journal of Global Economy, Business and Finance, 2025)
Industry 4.0 will bring extensive changes in the nature of work. While automation is likely to displace workers, new occupations will be created, which means the workers must be trained in new competencies and skills for production practices at the enterprises and the labor market in the globalization context. In addition, adequate collaboration between enterprises and vocational education institutions would lead to provision of relevant practical skills for industrialization. This article presents the survey results on Updating new skills-new technologies in training programs: A case study in Vietnam under the impact of the 4th industrial revolution and the level of combination between enterprises and vocational education institutes in training programs with 3 groups of occupations: 1-Information technology, electronics and telecommunications; 2-Electricity, electronics; Automation; 3-Agriculture, forestry and fishery. The questionnaire survey was conducted in two forms: online and in person at 700 enterprises, 50 TVET institutes and 7, 000 employees in 22 localities in Vietnam. The survey results are the basis for vocational training management agencies to make policies for vocational education so as to improve the quality of human resources, in line with Industry 4.0.